Empirical study on service quality and student satisfaction at YSCT - Azilah Baddiri; Clarice Duasin; Caroline Satu; Rohani Mamat; Mazlinda Musa; Chung Su Chin; Tri Sumarsih; Baidi Baddiri (Global Academic Excellence, 2024)
In today’s competitive environment, the education has not only become a major industry and need of the day but it is also an investment by the parents for their children. In public as well as in private sector, the quality of education is an important factor that considered for attracting and retaining the students who want to get higher education. It is obvious that customers are important stakeholders in organizations and their satisfaction is a priority to management. Customer satisfaction has been a subject of great interest to organizations and researchers alike. In recent years, organizations are obliged to render more services in addition to their offers. The quality of service has become an aspect of customer satisfaction. It has been proven by some researchers that service quality is related to customer satisfaction. The main purpose of this study is to identify the level of service quality as perceived by students in the YSCT and to identify the level of student satisfactions towards service quality. Purposive and simple randomized sampling technique was used to collect quantitative data from customers of Yayasan Sabah College of Technology (YSCT) to get their satisfaction levels and level of service quality which were substituted in the SERVQUAL model. This study contributes to existing theories by confirming or adding value to the relationships that are involved in customer satisfaction, service quality and SERVQUAL dimensions. It provides results that could be useful to top management in business organizations for strategic planning